Evaluate factors effecting claims management operation in car insurance of Bao Viet Insurance ( 2012-2016 ) - Pham, Viet Hung (Khoa Quốc tế, ĐHQGHN, 2019)
Studying on the Claim management in Bao Viet Insurance is an urgent requirement in the operational process of the insurance industry in general and Bao Viet in particular, meeting the requirements of business efficiency, Bao Viet brand name value and level of competition